The relationship between physical activity, mental wellbeing and symptoms of mental health disorder in adolescents: a cohort study - Bell, Sarah Louise (Int J Behav Nutr Phys Act, 2019)
BACKGROUND: Mental illness is a worldwide public health concern. In the UK, there is a high prevalence of mental illness and poor mental wellbeing among young people. The aim of this study was to investigate whether physical activity is associated with better mental wellbeing and reduced symptoms of mental health disorder in adolescents. METHODS: A cohort of 928 12–13 year olds (Year 8) from six secondary schools in England, who had participated in the AHEAD trial, ‘Activity and Healthy Eating in Adolescence’, were followed up three years later (when 15–16 years old, Year 11). At baseline, physical activity was measured using accelerometers. At follow-up, mental wellbeing was measured using the ‘Warwick Edinburgh Mental Wellbeing Scale’ (WEMWBS) and symptoms of mental health disorder using the ‘Strengths and Difficulties Questionnaire’ (SDQ). Multivariable linear regression analyses were used to investigate associations between physical activity and both mental wellbeing and symptoms of mental health disorder. RESULTS: 794 (86%) of the eligible 928 young people provided valid accelerometer data at baseline. 668 (72%) provided complete mental wellbeing data and 673 (73%) provided complete symptoms of mental health disorder data at follow-up. The multivariable analyses showed no evidence of an association between physical activity volume (counts per minute (cpm)) or intensity (Moderate to Vigorous Physical Activity (MVPA)) and mental wellbeing (WEMWBS overall score) or overall symptoms of mental health disorder (SDQ Total Difficulties Score). However, higher levels of physical activity volume at age 12–13 years were associated with lower scores on the emotional problems subscale of the SDQ at age 15–16 years. CONCLUSIONS: This cohort study found no strong evidence that physical activity is associated with better mental wellbeing or reduced symptoms of mental health disorder in adolescents. However, a protective association between physical activity and the emotional problems subscale of the SDQ was found. This suggests that physical activity has the potential to reduce symptoms of depression and anxiety in adolescents. Future cohort study designs should allow for repeated measures to fully explore the temporal nature of any relationship.